Virus–Host Interactions and Genetic Exchange in Mixed Infections of Tomato Yellow Leaf Curl Virus (TYLCV), Tomato Leaf Curl New Delhi Virus (ToLCNDV), and Tomato Chlorosis Virus (ToCV) - Isabel M. Fortes; Luis Díaz-Martínez; Enrique Moriones; Ana Grande-Pérez (Agronomy)
Tomato yellow leaf curl virus (TYLCV), tomato leaf curl New Delhi virus (ToLCNDV), and tomato chlorosis virus (ToCV) are emerging viruses that cause significant damage to tomato (Solanum lycopersicum). TYLCV and ToLCNDV are single-stranded DNA viruses from the genus Begomovirus, family Geminiviridae, while ToCV is an RNA virus from the genus Crinivirus (family Closteroviridae). These viruses share overlapping geographic ranges, vectors (the whitefly Bemisia tabaci), and host plants, making mixed infections common. This study investigated interactions between TYLCV and ToLCNDV and between ToLCNDV and ToCV in mixed infections of susceptible and TYLCV-resistant tomato genotypes. We evaluated infection, disease development, trans-replication of genome components, and genetic exchange. Our results showed no significant synergistic or antagonistic interactions, complementation, or interference between the viruses. TYLCV resistance in tomato genotypes remained stable. The DNA-B component of ToLCNDV exhibited impaired functionality and was not complemented by TYLCV. No evidence was found that the crinivirus tomato chlorosis virus (ToCV) enhances ToLCNDV infection, suggesting limited interactions despite shared vectors. Genetic exchange was detected in defective DNA (def-DNA) molecules using high-throughput sequencing (HTS), indicating potential genetic interactions between these viruses. These findings suggest that mixed infections do not pose immediate concerns for increased pathogenicity but highlight the ecological implications of genetic exchange, warranting further study of the evolutionary consequences of such interactions in mixed-virus environments.